MOLECULAR DETECTION OF BURKHOLDERIA MALLEI IN NASAL SWABS FROM DRAUGHT HORSES WITH SIGNS OF RESPIRATORY TRACT INFECTION - M. T. Ghori; M. S. Khan; J. A. Khan; M. Rabbani; M. H. Chaudhary; M. Z. Shabbir; R. Ahmed; H. R. Chaudhry; J. Muhammad (Journal of Animal and Plant Sciences, 2018)
Glanders is a highly contagious and fatal zoonotic bacterial infection of equines. The disease is endemic in South Asia. The nasal shedding of bacteria from infected carrier animals may spread disease in susceptible hosts. The purpose of this study was to determine mallein reactivity in glanders suspected draught horses and estimate prevalence of active nasal shedders. A total of n=122 animals were purposively selected based on a case definition. Initially, the horses were screened through mallein test and later their nasal swabs were tested by real time PCR for the detection of B. mallei DNA. Mallein test was positive in 35.24 % (95% CI: 26.8%-43.7) animals. B. mallei was detected in only two horses. To explore pattern of clinical symptoms, Principal component analysis (PCA) was carried out. PCA clustered correlated symptoms into principal components. PCA confirmed co-occurrence of nasal and skin forms of disease in most horses included in the study. The study found high prevalence of the disease and existence of active nasal shedders in draught horses. PCA grouped symptoms that were more correlated together and provides a mechanism to overcome collinearity for regression models. The findings implicate importance of targeted surveillance in glanders suspected horses. of mortality, the lack of effective treatment; and
Keywords: Burkholderia mallei; draught horses; mallein test; real time PCR; PCA analysis.